2006
DOI: 10.1212/01.wnl.0000210487.36667.a5
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion MRI abnormalities after prolonged febrile seizures with encephalopathy

Abstract: Although the pathophysiologic mechanism remains unknown, these patients seem to have a distinctive encephalopathy syndrome. MRI is helpful in establishing the diagnosis of this encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
182
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(192 citation statements)
references
References 13 publications
4
182
1
Order By: Relevance
“…In this study, central-sparing lesions were not observed in any patient within the first 3 days after onset, consistent with several previous reports. 3,[12][13][14]17 In contrast, frontal occipital lesions were recognized within the first 3 days after onset and were followed by diffuse lesions. Second, the distribution of brain lesions is different in the 2 situations.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In this study, central-sparing lesions were not observed in any patient within the first 3 days after onset, consistent with several previous reports. 3,[12][13][14]17 In contrast, frontal occipital lesions were recognized within the first 3 days after onset and were followed by diffuse lesions. Second, the distribution of brain lesions is different in the 2 situations.…”
Section: Discussionmentioning
confidence: 97%
“…A biphasic clinical course is characteristic of this group of patients, as described previously. 3 Several studies on acute encephalopathy have also reported a biphasic clinical course. [11][12][13][14] Onset is often marked by a prolonged seizure followed by improved consciousness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations